Penentuan Rute Distribusi Produksi Roti yang Optimal Menggunakan Model Vehicle Routing Problem (VRP) dengan Metode Saving Matrix Pada PT. XYZ - Sugiono, Mohammad Cipto; Siswiyanti, Siswiyanti; Abdul Ghoni, Sukma (Universitas Pamulang, 2025)
The problem in transportation is the Vehicle Routing Problem (VRP), the delivery process of bread production at PT. XYZ is known to have not implemented an optimal distribution system. The purpose of writing this thesis is to create a VRP model for the distribution route in PT XYZ, completing it using the saving matrix, nearest insert and nearest neighbour methods. The saving matrix method uses the saving value, the nearest insert method adds a new point to the existing route, while the nearest neighbour method considers the nearest distance. The calculation carried out using the VRP model with the saving matrix method resulted in a distance saving of 82.284 km, then the nearest insert resulted in a distance saving of 93.829 km, and the nearest neighbor resulted in the largest distance saving, namely 94.406 km, with vehicle route 1 Factory-Wonokerto-Pringlangu-Landungsari-Poncol-Factory, vehicle route 2 is Factory-Grogol-Talang-Adiwerna-Slawi-Factory, vehicle route 3 is Factory-Poso-Randugunting-Kraton-Factory, and vehicle route 4 is Factory-Mejasem-Kemantran-Brebes-Factory. The proposed distribution route received the largest decrease, which was 94.406 km, initially the company's mileage was 285.414 km. The calculation of the route saving percentage is 33% and saves costs of Rp. 235,284 thus the optimal route.